Establishing Judicial Authority Through Citation Network Analysis of Appellate Court Decisions - Hoole, E.J. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
The identification of authoritative judgments—those judicial decisions widely recognized for their binding influence on subsequent legal reasoning—is a cornerstone of jurisprudence. In Sri Lanka, the authority of appellate court decisions often emerges implicitly through frequent citation by legal practitioners and judges. However, systematic efforts to delineate such authoritative judgments and establish a structured taxonomy remain limited. This study addresses this gap through a computer-aided citation network analysis of over 20,000 Sri Lankan appellate court decisions, spanning the years 1880 to 2024, including a collection of over 9,000 unreported decisions. Our contributions are threefold: (i) identifying the 1,000 most frequently cited appellate judgments; (ii) categorizing these judgments by legal domain; and (iii) mapping the specific legal questions resolved by each decision. By offering an empirical foundation for assessing judicial authority, this research advances the understanding of Sri Lankan case law and its jurisprudential evolution.
Keywords: e-justice; Legal AI; Citation network analysis; Judicial authority; Jurisprudence